2015
DOI: 10.1371/journal.pone.0138535
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 Protects Pancreatic Beta Cells from Cytokine- and Streptozotocin-Mediated Cell Death

Abstract: A hallmark feature of type 1 and type 2 diabetes mellitus is the progressive dysfunction and loss of insulin-producing pancreatic beta cells, and inflammatory cytokines are known to trigger beta cell death. Here we asked whether the anti-oxidant protein DJ-1 encoded by the Parkinson’s disease gene PARK7 protects islet cells from cytokine- and streptozotocin-mediated cell death. Wild type and DJ-1 knockout mice (KO) were treated with multiple low doses of streptozotocin (MLDS) to induce inflammatory beta cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…It is well known that obesity is one of the most important risk factors for T2DM, and ectopic fat accumulation can induce glucose metabolism disorder and insulin resistance 18 . Previous articles also reported that DJ-1 has a moderating effect on T2DM 10 , 12 , 19 , 20 . In the present study, deletion of DJ-1 ameliorated glucose metabolism and insulin sensitivity in HFD-induced mice model.…”
Section: Discussionmentioning
confidence: 85%
“…It is well known that obesity is one of the most important risk factors for T2DM, and ectopic fat accumulation can induce glucose metabolism disorder and insulin resistance 18 . Previous articles also reported that DJ-1 has a moderating effect on T2DM 10 , 12 , 19 , 20 . In the present study, deletion of DJ-1 ameliorated glucose metabolism and insulin sensitivity in HFD-induced mice model.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, knockdown of DJ-1 in the cells by the small interfering RNA markedly reduced cell survival under same experimental conditions (Inberg and Linial, 2010 ). Other reports have shown that DJ-1 protein significantly protected against STZ-induced or cytokine-induced pancreatic β-cell death in DJ-1 knockout mice, leading the authors to suggest that the DJ-1 is required to protect against oxidative stress including STZ and cytokine-induced β-cell death (Inberg and Linial, 2010 ; Jain et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other studies have shown that DJ-1 protects against pancreatic β-cell death in STZ-exposed mice. In DJ-1 KO mice, insulin levels are significantly lower compared to those in STZ-treated mice ( 27 ). Other studies have shown that high glucose levels and FFA affect β-cell functionality and survival throughout the course of DM.…”
Section: Resultsmentioning
confidence: 99%